2012
DOI: 10.1007/s00345-012-0926-x
|View full text |Cite
|
Sign up to set email alerts
|

Patients with prostate cancer treated by ADT have significantly higher fibrinogenemia than healthy control

Abstract: This is the first study that demonstrates the significant increase in FB in PCa patients on ADT, while CRP as inflammatory marker did not increase. Elevation of SF may contribute to increased CVR in PCa patients. Further prospective studies are warranted to confirm this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Thus, there may be residual confounding affecting the analysis of those on anti-androgen monotherapy. Alterations in lipid levels may be another mechanism through which systemic ADT is propagating risk of TED [26][27][28][29][30]. Our dataset does not contain information on any of these factors and thus further mechanistic studies are required to determine if these do play a role in the associations observed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, there may be residual confounding affecting the analysis of those on anti-androgen monotherapy. Alterations in lipid levels may be another mechanism through which systemic ADT is propagating risk of TED [26][27][28][29][30]. Our dataset does not contain information on any of these factors and thus further mechanistic studies are required to determine if these do play a role in the associations observed.…”
Section: Discussionmentioning
confidence: 99%
“…25 Hypercoagulability is a direct pathophysiological factor contributing to symptomatic TE and CV complications. 26,27 However, increased intravascular hypercoagulability, a proposed mechanism of early TE events in cancer patients, has not been examined systematically in association with ADT.…”
Section: Discussionmentioning
confidence: 99%
“…27 However, this study did not use TEG as a global, sensitive measure of hypercoagulability and did not include PCa patients on watchful waiting as controls. The findings in the current study may complicate consideration of management of the potential hypercoagulable state in PCa patients relative to previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive study allow definitively determine the diagnostic and prognostic markers with the highest informative value suitable not only for urinary bladder cancer, but also for other malignancies (Cariaga-Martinez et al, 2013;Ziaran et al, 2013).…”
Section: Disscussionmentioning
confidence: 99%